Survival in Parkinson's disease in relation to striatal dopamine transporter binding - Mäkinen E; Joutsa J; Vahlberg T; Kaasinen V (ELSEVIER SCI LTD, 2022)
Objective: To investigate whether dopamine transporter (DAT) binding, as measured with single photon emission computed tomography (SPECT), can be used to predict mortality in patients with Parkinson's disease (PD). Methods: A total of 162 patients with PD and abnormal [I-123]FP-CIT SPECT were clinically followed for a median of 5.8 years. A multivariate Cox regression model was used to investigate survival with the independent predictors of age, gender, severity of motor impairment, levodopa-equivalent daily dose of medication, presence of cognitive defects, and putaminal specific binding ratio (SBR) of [I-123]FP-CIT. In addition, associations between striatal and extrastriatal SBRs and survival were investigated using voxel-based analyses.Results: The overall mortality was 25.9%, and the Kaplan-Meier estimate for mortality was 36%. Older age (P< 0.001), presence of cognitive defects (P = 0.001), and more severe motor symptom severity (P = 0.002) were significantly associated with increased mortality. No associations were found between putaminal DAT binding and survival (P = 0.99). There were no significant differences in SBRs in any striatal or extrastriatal region between survivors and non-survivors, and no associations were found between SBRs and scan-to-death intervals among non-survivors.Conclusions: Unlike the severity of motor and cognitive symptoms, the level of striatal dopaminergic defect in DAT SPECT does not predict mortality in PD. Although presynaptic dopaminergic functional imaging may have value as a diagnostic tool, the clinical symptom-based characteristics are superior for predicting lifespan. (c) 2017 Elsevier Ltd. All rights reserved.